Comparison of Two Time-Integration Algorithms for an Anisotropic Damage Model Coupled with Plasticity - Reese, Stefanie; Fassin, Marek; Wulfinghoff, Stephan (Applied Mechanics and Materials, 2015)
In this work, two time integration algorithms for the anisotropic damage model proposed by Lemaitre et al. (2000) are compared. Specifically, the standard implicit Euler scheme is compared to an algorithm which implicitly solves the elasto-plastic evolution equations and explicitly computes the damage update. To this end, a three dimensional bending example is solved using the finite element method and the results of the two algorithms are compared for different time step sizes.